EXPONENTIAL ABSORPTION SPECTRUM AND DENSITY DISTRIBUTION OF ELECTRONIC STATES ON THE TAIL OF THE VALENCE ZONE OF AMORPHOUS SEMICONDUCTORS - Muminov Khurshidbek Adhamjon ugli, Otamirzaev Doniyor Rustam ugli, Saloydinov Sardorjon Qodirjon ugli (Research Focus International Scientific Journal, 2022)
The analytical expression of the spectrum, derived for the region of exponential absorption of amorphous semiconductors, is investigated. The parameters in this expression that determine the slope of the tails of the allowed bands are determined by fitting to the exponential absorption spectrum, which are determined experimentally. For the Davis-Mott approximation, a new formula is derived from the Kubo-Greenwood formula, which determines the densities of electronic states at the tail of the valence band. Using these formulas and the experimentally determined exponential absorption spectrum, it is shown that it is possible to determine the density of electronic states at the tail of the valence band.